Effectiveness of Massage Techniques in Managing Acute Pain in Patient Mr. E with Tertian Malaria in Class I & II Wards at Serui Regional General Hospital (Journal of Social And Education Research, 2025)
Malaria remains a significant global health problem, with approximately 247 million cases and 619,000 deaths worldwide in 2023. Indonesia, particularly in eastern regions such as Papua, has a high malaria endemicity, with an Annual Parasite Incidence (API) of 42.65 per 1,000 population, far exceeding the national average of 0.84 per 1,000 population. This case study aims to evaluate the effectiveness of massage techniques in managing acute pain in Mr. E, a patient with tertian malaria, in Class I & II wards at Serui Regional General Hospital, Papua, on February 18–19, 2025. The study employed a case study design using a nursing process approach. Data were collected through interviews, observation, physical examination, and documentation review. Research instruments included a nursing assessment form, Numeric Rating Scale (NRS), observation sheets, and nursing care documentation formats. The application of massage techniques combined with pharmacological therapy effectively managed acute pain, resulting in a reduction in pain intensity from a scale of 3 to 1 after two days of implementation. Massage techniques proved to be an effective non-pharmacological approach for managing acute pain in patients with tertian malaria, enhancing patient comfort.